CERVICAL DISC REPLACEMENT WITH POLYETHERETHERKETONE CAGES: CLINICAL EXPERIENCE WITH 151 CASES - Junaid, Muhammad; Kalsoom, Anisa; Khalid, Muhammad; Bukhari, Syed Sarmad (Journal of Ayub Medical College Abbottabad, 2014)
Background: There is active debate amongst surgeons regarding best available method for cervical inter-body fusion. This study evaluates success of disc replacement with polyetheretherketone (PEEK) cage in patients operated for cervical radiculopathy or myelopathy. Methods: This case series was conducted between 2008 and 2012 during which 151 patients were treated with cervical inter-body fusion with PEEK cages. PEEK cages were packed with cancellous bone taken from iliac crest. The duration of follow up was 1 year. Subsidence, fusion, cage migration, and/or breakage were assessed using serial cervical X-Rays. Results: Mean age was 42.6 years with standard deviation of 9.37. No implant insufficiency was observed in any case while fusion rate was 100%. Conclusion: Many techniques and materials are available for use in vertebral inter-body fusion. The use of PEEK cage seems to be a good alternative in that it has minimal complications and gives excellent results in skilled hands and gives results comparable to other options. Keywords: Cervical discectomy, inter body implant, PEEK cage